Molecular structure of guanine-quartet supramolecular assemblies in a gel-state based on a DFT calculation of infrared and vibrational circular dichroism spectra - Setnicka, Vladimír; Nový, Jakub; Böhm, Stanislav; Sreenivasachary, Nampally; Urbanová, Marie; Volka, Karel (Langmuir, 2008)
The infrared (IR) and vibrational circular dichroism (VCD) spectra of guanosine-5'-hydrazide ( G-1), a powerful hydrogelator, have been measured and analyzed on the basis of ab initio modeling. B3LYP/6-31G** DFT calculations predict that G-1, forming a clear solution in deuterated DMSO, is present in monomeric form in this solvent, whereas strong gelation in a phosphate buffer is due to the formation of a guanine-quartet structure, ( G-1)4, in which the four G-1 are linked by hydrogen-bonded guanine moieties and stabilized by an alkali metal cation. The B3LYP/6-31G** IR and VCD spectra of the nearly planar G-quartet, whose structure is slightly distorted from the C4h symmetry, in which the G-bases interact via four Hoogsteen-type hydrogen bonds and a sodium cation is positioned in the middle of the G-quartet, are in very good agreement with the experimental spectra, indicating that this structure is the predominant structure in the gel state. The geometric parameters are discussed. This study is the first to use IR and VCD spectroscopies coupled with DFT calculations to elucidate the structure of a supramolecular species in a gel state and shows the VCD spectroscopy as a powerful method for investigating the structure of complex supramolecular self-assemblies where the use of other structural methods is limited.
Keywords: sacharidy; dimerizace; Circular Dichroism; Guanine; Models, Molecular; Molecular Structure; cirkulární dichroismus; Gels; Spectrophotometry, Infrared; spektrofotometrie infračervená; Dimerization; guanin; Carbohydrates; Vibration; molekulární modely; gely; molekulární struktura; vibrace